A Recent Update on the Clinical Trials and Effectiveness of Drugs Used in COVID-19, MERS and SARS Coronaviruses - Balef, Seyed S. H.; Karimi, Zohreh; Azari, Aala; Sadraei, Seyed S.; Hasanjani, Parisa; Sadeghi, Yasaman; Ahmadi, Samin; Qorbannejad, Fateme; Farmoudeh, Ali; Irannejad, Hamid (Anti-Infective Agents, 2022)
Background: Coronaviruses including COVID-19, MERS and SARS have affected millions of people around the world since their emergence. Still, there is not a certain drug treatment strategy for coronaviruses. Objective: This review aims at a compilation of a comprehensive study on literature reporting the treatment strategies and regimens used for COVID-19, MERS and SARS with an emphasis on the clinical trials and experimentations. Results: According to the literature, the most effective drugs reported so far for treatment strategies include: lopinavir/ritonavir, favipiravir, ribavirin, oseltamivir, remdesivir, hydroxychloroquine, herbal extracts, monoclonal antibodies and anticytokine agents. Some combinations of drugs have been very effective to reduce the death rate, hospitalization stay and to prevent the progress of the disease to the later critical and severe stages. Conclusions: However, a combination of drugs and regimens have been useful and saved millions of patient’s lives but the clinical data reviewed in this essay indicate that the current drugs do not make an impervious barrier against coronavirus infections and cannot protect or treat patients completely. Therefore, there is a much demand for the discovery and introduction of new antiviral drugs.
Keywords: MERS